Protect Incomes or Protect Jobs? The Role of Social Policies in Post-Pandemic Recovery - Demirgüç-Kunt, Asli; Lokshin, Michael; Torre, Iván (World Bank, Washington, DC, 2022)
This paper examines the effectiveness of income protection and job protection policies for the post-pandemic economic recovery of the second half of 2020 through 2021. The paper is based on a new data set of the budgets of social protection programs implemented as a part of the pandemic stimulus package in 154 countries. The empirical analysis shows that, in the short run, higher expenditure on job protection measures is associated with more robust gross domestic product growth, increased employment, and decreased inactivity and poverty rates compared to the expansion of income protection programs. Both policies had a significant economic impact only in countries with weaker pre-pandemic social insurance systems. In countries with broader coverage of the social insurance system, the income and job protection programs appear to have had a limited impact on post-pandemic recovery. Because the structural economic changes induced by the pandemic are expected to materialize fully in several years, more research is needed to understand the longer-term effects of job protection and income protection policies on labor markets and economic recovery.